2013
DOI: 10.1039/c3cc45949g
|View full text |Cite
|
Sign up to set email alerts
|

An asymmetric tubular ceramic-carbonate dual phase membrane for high temperature CO2 separation

Abstract: For the first time, a tubular asymmetric ceramic-carbonate dual phase membrane was prepared by a centrifugal casting technique and used for high temperature CO2 separation. This membrane shows high CO2 permeation flux and permeance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 26 publications
(10 reference statements)
1
54
1
Order By: Relevance
“…29 From the equilibrium 4OH(g) ⇔ O 2 (g) + 2H 2 O(g), [9] the emf related to OH − for small gradients can be expressed as: Approaches to correction for electrode polarization.-If the transport number of native ions is not unity, there will be a significant transport number of electrons or some foreign ionic species. A chemical gradient will then result in a net flux by ambipolar transport through the sample.…”
Section: Transport Number Measurementsmentioning
confidence: 99%
“…29 From the equilibrium 4OH(g) ⇔ O 2 (g) + 2H 2 O(g), [9] the emf related to OH − for small gradients can be expressed as: Approaches to correction for electrode polarization.-If the transport number of native ions is not unity, there will be a significant transport number of electrons or some foreign ionic species. A chemical gradient will then result in a net flux by ambipolar transport through the sample.…”
Section: Transport Number Measurementsmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19] The first class is a mixed oxide-ion and carbonate-ion conductor (MOCC) comprised of an oxide and carbonate phase. The second class is a mixed electron and carbonate-ion conductor (MECC) consisted of a metal and carbonate phase.…”
mentioning
confidence: 99%
“…Within the two new electrochemical membranes, the MECC membrane technology is of particular interest because of its ability to capture CO 2 from a flue gas stream emitted from coal-fired power plants; [17][18][19] the latter is one of the major industrial emitters of CO 2 . However, our previous work showed that the flux of MECC membranes was unstable for a longer period of time to have any practical implications.…”
mentioning
confidence: 99%
“…The membrane module also demonstrated good long-term stability in actual coal-derived syngas streams with 320 ppm H 2 S. The polymeric membranes cannot be used at high temperatures. The membranes with reduced thickness prepared in tubular geometry (Dong, Ortiz-Landeros, & Lin, 2013) showed improved CO 2 permeance at temperatures above 800 K. Anderson and Lin (2013) demonstrated the use of such a dual-phase membrane for hydrogen (syngas) production by dry-reforming. The membranes permeate CO 2 with O 2 , but not other gases at temperatures above 700 K. However, the membranes are not stable because stainless steel can be oxidized and also reacts with molten carbonate.…”
Section: Co 2 -Selective Membranesmentioning
confidence: 96%